Kinerja Keuangan Pada PT. Telekomunikasi Indonesia (Persero) Tbk Periode 2019-2022 - Lailatus Sa’adah; Ardila Rustafi’ah (Pusat Riset dan Inovasi Nasional, 2024)
This study discusses the Analysis of Liquidity Ratios, Solvency, Activity, Profitability.To measure financial performance at PT. TELECOMMUNICATIONS INDONESIA (Persero) Tbk., while the purpose of this study was to determine the condition and performance based on financial ratios. The objects used in this research are financial reports in the form of balance sheets and profit and loss reports at PT. TELECOMMUNICATIONS INDONESIA (Persero) Tbk. Period 2019-2022. The data analysis method used is the quantitative data analysis method.The results of the study were seen from the liquidity ratio in 2019-2022, the conditions were not good. In terms of solvency ratio, the condition of the company is good. In the activity ratio, the company's condition is not good because the calculation using the ratio of Total Asset Turn over, Average collections period, and Fixed Asset Turn Over shows a bad value. The profitability ratio can be said to be unfavorable because the profitability ratio analysis calculation shows that the company has not met the specified industry average standards because the profitability ratio analysis is measured using the ratio of Gross Profit Margin, Net Profit Margin, and Operating Ratio showing the same value. is not good, it can be seen that the overall level of profitability ratios is still not good.